Effect of anterior cruciate ligament reconstruction with hamstring tendons on Insall-Salvati index and anterior knee pain - Korkmaz, Özgür; Malkoç, Melih (Srpsko Lekarsko Drustvo, 2018)
Introduction/Objective The relationship between anterior knee pain and the Insall-Salvati ratio after anterior cruciate ligament (ACL) reconstruction with hamstring tendon were evaluated in this study. Methods We evaluated 39 patients that had an ACL reconstruction surgery with hamstring tendon. All the patients were evaluated for the Insall-Salvati ratio preoperatively and postoperatively. Fourteen patients had anterior knee pain at the end of the first year after the surgery. The patients were evaluated at the end of the first year after the surgery with the Lysholm score and the Tegner activity scale. The patients' preoperative and postoperative measurements were analyzed by using the Wilcoxon test, and the differences between the patients with anterior knee pain and those without it were analyzed by the Mann-Whitney U test. Results Preoperatively, mean Insall-Salvati ratio was found to be 0.91 +/- 0.1, whereas postoperative ratio was 0.85 +/- 0.09 (p <= 0.05). In the group without anterior knee pain, the mean Tegner activity score was 8.56 +/- 1.04, and the mean Lysholm score was 87.36 +/- 9.42. The mean Tegner activity score was 7.21 +/- 0.97 and the mean Lysholm score was 74.43 +/- 9.94 in the group with anterior pain. There was a decrease in the Insall-Salvati ratio as a result of the surgery, but patients with anterior knee pain had lower values of the Insall-Salvati ratio preoperatively. Conclusion Low preoperative Insall-Salvati ratio can be an indicator of anterior knee pain in the early period after ACL reconstruction with hamstring tendons. The mean Tegner activity score and the mean Lysholm score have higher values in the group without anterior pain postoperatively.
WOS: 000436254500009
Keywords: Anterior Cruciate Ligament; Reconstruction; Insall Salvati Index; Hamstring Tendons